Congenital Anomalies of the Nose - Funamura, Jamie L.; Tollefson, Travis T. (Facial Plastic Surgery, 2016)
Congenital anomalies of the nose range from complete aplasia of the nose to duplications and nasal masses. Nasal development is the result of a complex embryologic patterning and fusion of multiple primordial structures. Loss of signaling proteins or failure of migration or proliferation can result in structural anomalies with significant cosmetic and functional consequences. Congenital anomalies of the nose can be categorized into four broad categories: (1) aplastic or hypoplastic, (2) hyperplastic or duplications, (3) clefts, and (4) nasal masses. Our knowledge of the embryologic origin of these anomalies helps dictate subsequent work-up for associated conditions, and the appropriate treatment or surgical approach to manage newborns and children with these anomalies.
Keywords: nasal deformities; nasal dermoid; Tessier cleft; nasal cleft; nasal hemangioma